Determinants of Customer Satisfaction toward Shopee: A Case Study In Malaysia - Haslindar Ibrahim; Rudresh Pandey; Hor Xin Pang; Yibo Peng; Shi Ling Pung; Puteri Nabila Asyhah Roslan; Somya Srivastava (AIBPM Publisher, 2026)
The rapid expansion of e-commerce platforms like Shopee among Malaysians and which was also among the top online marketplace that alters the consumer purchasing habits in the country. This research is conducted to investigate the factors that influenced customer satisfaction with Shopee in Malaysia. It examines the impact of users’ perceptions on their satisfaction in e-commerce platforms such as Shopee. This study investigates the effects of perceived usefulness, perceived ease of use, perceived trust and perceived convenience on customer satisfaction. In our study, a quantitative survey will be carried out via Google Forms for the Shopee users. The study was held for 250 respondents. The descriptive as well as inferential statistics including regression analysis and SPSS were employed for analyzing response. A key finding is that perceived trust is the most salient factor, followed by perceived usefulness, perceived convenience and perceived ease of use. The findings offer useful implications for the e-commerce platform to enhance user experience from the aspect of platform security and operational reliability with additional service to retain customer’s loyalty in the long run.